The effects of monetary policy on the Islamic financial services industry - Yungucu, Burak; Saiti, Buerhan (Emerald Group Publishing Limited, 2016)
Purpose – The purpose of this paper is to investigate the effects of monetary policy on the Islamic financial service industry by studying the findings of the existed literature. Design/methodology/approach – Because of the unavailability of the empirical models in the existing study, the authors used past studies review and proposed a new theoretical model. Findings – Majority of these studies have documented the negative effects with the exception of a few. The transmission of the monetary policy has been taken place through interest rate risk, asset-liability mismatch, as well as deposit and financing instability. Furthermore, the examined studies have confirmed the viability of the Islamic monetary policy. Originality/value – The proposed model may offer some insights to policy makers if it is examined empirically